The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/ajmg.b.30989
|View full text |Cite
|
Sign up to set email alerts
|

Stathmin, a gene regulating neural plasticity, affects fear and anxiety processing in humans

Abstract: The identification of biological mechanisms underlying emotional behavior is crucial for our understanding of the pathogenesis of mental disorders. Besides genes modulating neural transmission and influencing amygdala reactivity and anxiety-related temperamental traits a different plasticity regulating genes affect interindividual differences in emotional regulation. Recently it has been demonstrated that stathmin, a regulator of microtubule formation which affects long-term potentiation (LTP), controls learne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 52 publications
3
47
0
Order By: Relevance
“…The changes in stathmin 1 are of interest, as stathmin 1 affects fear responses in mice, 22 and polymorphisms in the stathmin 1 gene have been identified that influence fear and anxiety responses as well as cognitive and affective processing in humans. 53,54 The finding that stathmin 1 is elevated in blast-exposed brain therefore provides a novel target for beginning to understand effects of blast on the brain at the molecular level.…”
Section: Figmentioning
confidence: 99%
“…The changes in stathmin 1 are of interest, as stathmin 1 affects fear responses in mice, 22 and polymorphisms in the stathmin 1 gene have been identified that influence fear and anxiety responses as well as cognitive and affective processing in humans. 53,54 The finding that stathmin 1 is elevated in blast-exposed brain therefore provides a novel target for beginning to understand effects of blast on the brain at the molecular level.…”
Section: Figmentioning
confidence: 99%
“…Ample evidence illustrates the amygdala's role in contextual learning under fear conditioning scenarios (Fanselow & LeDoux, 1999;Sah et al, 2008) in rodents (Chau, Prakapenka, Fleming, Davis, & Galvez, 2013;Flavell & Lee, 2012;Trogrlic, Wilson, Newman, & Murphy, 2011) and in human neuroimaging (Hughes & Shin, 2011) and lesion (Koenigs et al, 2008) studies. As none of the iEEG studies reviewed used a conditioning task, future iEEG research would benefit from employing context learning paradigms controlling for arousal, self-relevance, and threat in order to assess the full nature of selective encoding and potential contextual encoding in human amygdala neurons relative to fear and anxiety-related behaviors in healthy and clinical populations (Brocke et al, 2010).…”
Section: Clinical Significancementioning
confidence: 99%
“…Besides adrenaline, noradrenaline and steroid cortisol, the protein stathmin, encoded by the stathmin gene (STMN1), plays a crucial role. Stathmin knockout mice are significantly less sensitive to fear (both innate and learned) and show less anxiety when exposed to new and potentially dangerous situations (Brocke et al 2010;Martel et al 2008). Top athletes from the mythic past like Siegfried (who knew no fear) may now be seen as cases of stathmin deficiency, causing the Siegfried complex as it were, as the STMN1 genotype has functional relevance for the acquisition and expression of basic fear and anxiety responses also in humans (Brocke et al 2010).…”
Section: Coping With Anxiety: the Socio-technological World As Behavimentioning
confidence: 99%
“…Stathmin knockout mice are significantly less sensitive to fear (both innate and learned) and show less anxiety when exposed to new and potentially dangerous situations (Brocke et al 2010;Martel et al 2008). Top athletes from the mythic past like Siegfried (who knew no fear) may now be seen as cases of stathmin deficiency, causing the Siegfried complex as it were, as the STMN1 genotype has functional relevance for the acquisition and expression of basic fear and anxiety responses also in humans (Brocke et al 2010). Brain research has entered sport science as well, as exemplified by a recent book entitled The Athletic Brain: How Neuroscience is Revolutionising Sport and Can Help You Perform Better by Amit Katwala (2016), focusing on the plasticity of the brain, however: on the brain's ability to learn and on the ways in which sport changes your brain.…”
Section: Coping With Anxiety: the Socio-technological World As Behavimentioning
confidence: 99%